Tactile perceptions of digital textiles: A design research approach - Atkinson, Doug; Orzechowski, P.; Petreca, B.; Bianchi-Berthouze, N.; Watkins, P.; Baurley, S.; Padilla, S.; Chantler, M. (2013)
Current interactive media presentations of textiles provide an impoverished communication of their 'textile hand', that is their weight, drape, how they feel to touch. These are complex properties experienced through the visual, tactile, auditory and proprioceptive senses and are currently lost when textile materials are presented in interactive video. This paper offers a new perspective from which the production of multi-touch interactive video representations of the tactile qualities of materials is considered. Through an understanding of hand properties of textiles and how people inherently touch and handle them, we are able to develop methods to animate and bring these properties alive using design methods. Observational studies were conducted, noting gestures consumers used to evaluate textile hand. Replicating the appropriate textile deformations for these gestures in interactive video was explored as a design problem. The resulting digital textile swatches and their interactive behavior were then evaluated for their ability to communicate tactile qualities similar to those of the real textiles. Copyright © 2013 ACM.